OFFICIAL PROFESSIONAL OATHS - Saminjonov Mukhammadali (Galaxy International Interdisciplinary Research Journal, 2024)
In Uzbek linguoculture there is no special document in the form of a separate set of sectoral oaths. Oaths in each sphere of office are expressed in special laws related to that sphere. For example, Article 92 of the Constitution of the Republic of Uzbekistan states: "The President is considered to have assumed office from the moment he takes the following oath at a session of the Oliy Majlis of the Republic of Uzbekistan"